From Zero to Hero: Pineapple Energy Bar: Anti-Stunting, a Generation’s Savior - Faridatunnida, Wiwit; Triantoro, Ali Mushofa; Rayhan, Rayhan; Aulia, Intan; Amanda, Fadiah Salwa; Widodo, Lovetania Islamika; Widhianingtyas, Clara Haffadohllisa; Adibrata, Abhiseka Maheswara; Kusuma, Intan Zulis; Maulana, Naufal Qois; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Stunting is a global health problem caused by malnutrition. Indonesia has a high prevalence of stunting, especially in rural areas. This study aims to develop and utilize the "Pineapple Energy Bar" as a solution to prevent stunting in children in Kalisaleh Village. The methods used are Community Rural Participatory (CRP) and Asset-Based Community Development (ABCD), which involve the community in every stage of the study, from the initial assessment to production and distribution. The results show that the Pineapple Energy Bar, which is rich in protein, vitamins, and minerals, can meet the nutritional needs of children and raise public awareness of the importance of balanced nutrition. In addition, this program opens new business opportunities for the community and improves skills in product processing and marketing. Thus, the Pineapple Energy Bar is expected to reduce stunting rates and improve the quality of life of the Kalisaleh Village community.